2003
DOI: 10.1152/japplphysiol.00851.2002
|View full text |Cite
|
Sign up to set email alerts
|

Selected Contribution: Variation and heritability for the adaptational response to exercise in genetically heterogeneous rats

Abstract: Troxell, Michael Lee, Steven Loyal Britton, and Lauren Gerard Koch. Selected Contribution: Variation and heritability for the adaptational response to exercise in genetically heterogeneous rats. J Appl Physiol 94: 1674-1681, 2003. First published November 1, 2002 10.1152/japplphysiol.00851. 2002-Adaptational response to aerobic exercise was artificially selected for across one generation in a founder population of 20 female and 20 male genetically heterogeneous rats (N:NIH). Selection for low and high respon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
22
0
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 27 publications
(42 reference statements)
3
22
0
1
Order By: Relevance
“…To our knowledge, a standardized or commonly accepted method of progressive overload, which takes into account these key considerations, is currently unavailable. Previous investigations that have described a progressive overload have typically done so by increasing a combination of treadmill speed, incline, and exercise duration (Powers et al 1990;Criswell et al 1993;Mokelke et al 1997;Eddington et al 1998;Fiebig et al 1998;Demirel et al 1999;Noble et al 1999;Braga et al 2000;González et al 2000;Machida et al 2000;Jew and Moore 2002;Troxell et al 2003;Jafari et al 2005;Peres et al 2005;Ghanbari-Niaki 2006;Mueller and Hasser 2006;Yang et al 2006;Ghanbari-Niaki et al 2007;Leandro et al 2007;Mueller 2007;Harris et al 2008;Vichaiwong et al 2009;Eynan et al 2010). However, the descriptions of the increases in intensity or duration have often not been implemented in a systematic or standardized way, and as such a dose-response relationship cannot be discerned.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, a standardized or commonly accepted method of progressive overload, which takes into account these key considerations, is currently unavailable. Previous investigations that have described a progressive overload have typically done so by increasing a combination of treadmill speed, incline, and exercise duration (Powers et al 1990;Criswell et al 1993;Mokelke et al 1997;Eddington et al 1998;Fiebig et al 1998;Demirel et al 1999;Noble et al 1999;Braga et al 2000;González et al 2000;Machida et al 2000;Jew and Moore 2002;Troxell et al 2003;Jafari et al 2005;Peres et al 2005;Ghanbari-Niaki 2006;Mueller and Hasser 2006;Yang et al 2006;Ghanbari-Niaki et al 2007;Leandro et al 2007;Mueller 2007;Harris et al 2008;Vichaiwong et al 2009;Eynan et al 2010). However, the descriptions of the increases in intensity or duration have often not been implemented in a systematic or standardized way, and as such a dose-response relationship cannot be discerned.…”
Section: Discussionmentioning
confidence: 99%
“…In 2002, we initiated a large-scale bidirectional selection experiment for the response to exercise training in a laboratory rat population with wide genetic heterogeneity (N:NIH outcrossed stock) (27). A base population (n ϭ 152) was tested for maximal treadmill running capacity before and after receiving the same amount of a moderate standardized treadmill training stimulus over an 8-wk period (3 exercise sessions per week) (61). On average, training produced a 140-m gain in maximal running capacity with interindividual variation ranging in magnitude from Ϫ339 to ϩ627 m. Ten male and ten female rats that represented the extreme ends for training response (Ͼ1 SD) were bred at each successive generation to develop low response to training (LRT) and high response to training (HRT) selected lines.…”
Section: Continuedmentioning
confidence: 99%
“…Given these strain-dependent differences, quantitative trait locus (QTL) mapping has been used to identify QTL for intrinsic exercise capacity in rats and mice (37,65). In contrast, less is known about the change in exercise capacity with training across inbred strains of rodents (30,42,63). Large differences were reported for training responses across several inbred strains of rats, and these strain differences persisted whether training was performed at the same relative or absolute workload (30,63).…”
mentioning
confidence: 99%
“…In contrast, less is known about the change in exercise capacity with training across inbred strains of rodents (30,42,63). Large differences were reported for training responses across several inbred strains of rats, and these strain differences persisted whether training was performed at the same relative or absolute workload (30,63). Using a mouse model of exercise training, Massett and Berk (42) reported that the change in exercise capacity with training varied significantly across inbred (B6, Balb/cJ, and FVB) and hybrid mouse strains.…”
mentioning
confidence: 99%